UTD-PO Solution for E-Plane Radiation Pattern Calculation of Rectangular Horn Antennas With Rectangular-Shaped Corrugations - Jose Lorente-Lopez; Jose-Victor Rodriguez; Fernando Quesada-Pereira; Leandro Juan-Llacer; Ignacio Rodriguez-Rodriguez (IEEE Access, 2023)
Proposing a novel hybrid uniform theory of diffraction-physical optics (UTD-PO) formulation, we develop a method to calculate the E-plane radiation pattern of corrugated E-plane rectangular horn antennas with rectangular corrugations. We derive the technique from the estimation of the total field that reaches the emitting source (a magnetic current line), thereby assuming the impingement of a plane wave above the horn (reciprocity is applied). To validate our method, we compare the performance of the UTD-PO analysis with that of the electric field integral equation (EFIE) solved using the method of moments (MoM). Our method shows improved computational efficiency over EFIE and other numerical techniques that fully discretize the geometry.